Blood biomarkers and Ki-67 proliferation marker in breast cancer - A. A. Studenikina; E. S. Mikhaylova; S. A. Arkhipov; N. A. Varaksin; A. V. Proskura; A. I. Autenshlyus (Медицинская иммунология)
Metastasis is the leading cause of death in patients with breast cancer (BC). It is known that the lesion of regional lymph nodes by tumor cells is more common in tumors with higher proliferative activity. Moreover, there is literature evidence on effects of cytokines and proteins upon the migration potential of the tumor. The aim of our work was to study the correlation between the concentrations of cytokines, proteins, and expression of Ki-67 proliferation marker in breast cancer with histology of non-specific invasive carcinoma.On the basis of pathological findings, 16 patients had metastases in regional lymph nodes (group I), and 18 patients had no detectable metastases (group II). Solid-phase enzyme immunoassay was used to determine concentrations of 14 cytokines in the supernatants of immunocompetent blood cells, i.e., IL-2, IL-6, IL-8, IL-10, IL-17, IL-18, IL-1β, IL-1ra, TNFα, IFNγ, G-CSF, GM-CSF, VEGF and MCP-1, and concentrations of 6 proteins were determined in blood serum: estrogen and progesterone receptors, cadherin-E (CDH1), plasminogen activator type 1 (PAI-1), mucin 1 (MUC1), heat shock protein 90αA1 (HSP90αA1). Immunohistochemical study of Ki-67 expression was performed in paraffin sections of tumors using monoclonal antibodies.The study showed that Ki-67 expression in tumor tissues and blood concentrations of IL-6, IL-8, IL-1β and TNFα were higher in group I patients. On the contrary, blood concentrations of CDH1 and PAI-1 were higher in group II patients. It was found that Ki-67 showed both inverse correlations with CDH1 and PAI1, and direct correlations with IL-8 and TNFα. CDH1 had a direct correlation with PAI1, and inverse correlations with IL-6, IL-1β and TNFα. The studied cytokines showed direct correlations with each other. The analysis of ROC curves showed good quality and optimal values of the cut-off points for Ki-67 expression, cytokine and protein concentrations, thus allowing best prediction for detectable lymphatic metastasis.On the basis of these results, a quotient was proposed, which represents a ratio of CDH1 contents to the sum of IL-1β and TNFα concentrations in blood samples, which can help identification of the patients with breast cancer at risk for lymphatic metastasis.